Sedentary fish as indicators of changes in the river flow rate after impoundment - Yanne A. Mendes (Elsevier, 2021)
The natural flood pulse of the Amazon basin has been altered progressively by the installation of hydroelectric dams, which have had a potentially adverse impact on the local fauna. Fish are sensitive to environmental changes, and one the way to assess how they respond is through the analysis of life history traits, such as growth patterns and reproduction. Here, we evaluated the life history traits of two sedentary cichlids, Geophagus argyrostictus and Geophagus altifrons, in the middle Xingu River (upstream and downstream sectors) pre- and post-impoundment including the flood and low water hydrological seasons. The mass-length relationship, condition factor (K), gonadossomatic index (GSI), breeding season, gonadal stages, and the length at 50% sexual maturity (L50) were analyzed. Data on river flow rates and the characteristics of the fish were collected during the pre- and post-impoundment periods. Post-impoundment, the discharge of the Xingu decreased in downstream sector. During the pre-impoundment period, the K of G. argyrostictus and female G. altifrons was lower in the upstream sector in both seasons, but higher in the downstream sector to G. argyrostictus. The GSI was lower in the post-impoundment period in both sectors and seasons in G. argyrostictus, whereas in the G. altifrons females, it was higher in the downstream sector in the low water season, but lower in the upstream sector in both seasons. In G. argyrostictus, spawning occurred in a single phase and was restricted to the low water season in both periods, whereas in G. altifrons, spawning was multiple. There was a reduction in the frequency of immature individuals in the upstream sector post-impoundment. The L50 was lower, principally in the upstream sector, in both species. Our results indicate that the growth patterns and reproduction of the two populations has been impacted, especially in the endemic G. argyrostictus. The construction of dams thus appears to place endemic species under a greatest risk of extirpation. These results provide important insights for the improvement of fish resource monitoring and the development of adequate management techniques.